Absence of bones at birth - A diagnostic dilemma - Tyagi, Vernika; Jain, Ashish; Chopra, Abhishek (Indian Journal of Child Health, 2018)
We present a male stillborn baby, born with disproportionate body and omphalocele. The infantogram revealed the absence of mineralization of all the bones, except for a minimal ossification of the ribs and spine. The possibilities that can be considered in such a case of absent mineralization at birth are very few. A definite diagnosis can be made on detailed clinical examination and the specific pattern of bone mineralization. The classical phenotypic features, associated anomalies, and the pattern of mineralization facilitated in diagnosing the rare entity, boomerang syndrome. Although the diagnosis should be confirmed by genetic studies, it is important to know the classical phenotypic and radiological features of boomerang dysplasia as it is often mistaken as achondrogenesis.